Teaching Reading Skill by Using Think Pair Share Model - Marvira Aulia Harvianda; Endang Komariah (Research in English and Education Journal, 2020)
The objective of this study is to figure out whether Think Pair Share based on cooperative learning improves the students’ ability in reading comprehension skill or not. Experiment quantitative is used as the research design in this study. The population of this study is the third year students at SMA 6 Banda Aceh. The writer chose one class as the sample in this study. The data was collected by using tests and the results are analyzed by using statistical formula. The result showed that the use of Think Pair Share in the teaching reading to the third year students of SMA 6 Banda Aceh was successful. The result showed that the t-score (5.79) was higher than t-table (2.021). It indicates that the students in the experimental class who are taught by using Think Pair Share get better improvement than before they were taught by using Think Pair Share.